Maigret [videorecording (DVD)] : the complete series - Pearce, Ashley; East, Jon; Atkinson, Rowan; Staar, Leo; Dingwall, Shaun; Simenon, Georges, 1903-1989; Simenon, Georges, 1903-1989; Simenon, Georges, 1903-1989; Simenon, Georges, 1903-1989 (BBC, 2018)
Follows the cases of Paris chief inspector, Jules Maigret.